Peran Faktor Pengaruh Dinamika Organizational Commitment: Mengentaskan Melemahnya Eksistensi UKM Kuliner di Bogor - Elizabeth, Roosganda; Notosudjono, Didik; Yusnita, Nancy; Hamzah, Hamzah; Moeins, Anoesyirwan; Margaretha, Giovanni Inez Erika; Ivan, Geraldy Samuel (Universitas Galuh, 2024)
This research aims to identify and analyze the role and influence of the determinants of organizational commitment dynamics on the continued existence of culinary SMEs in Bogor; against the identified background of the weakening of its existence. Using mixed methods, this study randomly selected 210 samples using SEM (Structural Equation Modeling) and AHP-FAHP (Analytical Hierarchy Process-Fuzzy Analytical Hierarchy Process) analysis techniques. The research results show that perceived organizational support, creativity and employee work motivation are determining factors that have a significant influence on organizational commitment, which ultimately contributes to the resilience and growth of culinary SMEs in Bogor.